Associated risks of smoking and possible benefits of cessation in Covid-19: a rapid narrative review - Andrea Hernández-Pérez; Leonor García-Gómez; Sebastián Rodríguez-Llamazares; Ireri Thirión-Romero; Jennifer Osio-Echánove; Rogelio Pérez-Padilla (Instituto Nacional de Salud Pública, 2021)
Objective. To describe the possible risks associated to smoking in the spread and complications of Covid-19, emphasizing in the benefits of quitting smoking. Materials and methods. The narrative review methodology and the established process for Cochrane rapid reviews were used. Results. The scientific evidence related to smoking and Covid-19 remains limited. However, there is an already documented trend in cross-sectional, clinical studies and meta-analyses on the increased risk of adverse outcomes with Covid-19 associated with tobacco use. Conclusions. It is necessary to issue a warning that persons who smoke would have greater risks in the Covid-19 pandemic, which add to the many already known risks of tobacco use. Thus, quitting smoking becomes a relevant preventive measure to better confront SARS-CoV-2.